PENGARUH GAYA KEPEMIMPINAN DAN PENGAWASAN TERHADAP KINERJA PEGAWAI PADA KANTOR BADAN PERTANAHAN NASIONAL DI KABUPATEN KLUNGKUNG - Ni Komang Sri Megantari; Ni Wayan Eka Mitariani; I Gusti Ayu Imbayani (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2022)
Performance is a result of work achieved by an employee in accordance with predetermined standards and criteria within a certain period of time. The purpose of this study was to determine the effect of leadership style and the influence of supervision on employee performance at the National Land Agency Office in Klungkung district. The number of samples taken was 35 employees at the National Land Agency Office in Klungkung Regency with the saturated sampling method. Data was collected by observation, interviews, documentation studies and distributing questionnaires. The research instrument used is validity test and reliability test. The analysis technique used is the classical assumption test, multiple correlation test, analysis of determination, multiple linear regression analysis, F test and t test. Based on the results of the analysis of leadership style has a positive and significant effect on employee performance at the National Land Agency Office of Klungkung Regency. This is evidenced by the significance value of the t-test statistic of 0.001 < 0.050. Supervision has a positive and significant effect on employee performance at the National Land Agency Office of Klungkung Regency. This is evidenced by the significance value of the t-test statistic of 0.005 < 0.050. Leadership and supervision styles have a positive and significant effect on employee performance at the National Land Agency Office of Klungkung Regency. This is evidenced by the significance value of the F statistical test 0.000 < 0.050.